Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/irv.12472
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus‐like particles harboring H9N2 HA and NA proteins induce a protective immune response in chicken

Abstract: BackgroundAvian influenza viruses represent a growing threat of an influenza pandemic. The co‐circulation of multiple H9N2 genotypes over the past decade has been replaced by one predominant genotype—G57 genotype, which displays a changed antigenicity and improved adaptability in chickens. Effective H9N2 subtype avian influenza virus vaccines for poultry are urgently needed.ObjectiveIn this study, we constructed H9N2 subtype avian influenza virus‐like particle (VLP) and evaluated its protective efficacy in spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Although these are non-replicating particles, they retain the morphology of the virus and, therefore, the antigenicity and can activate innate immunity. VLPs can be produced in several expression systems, including baculovirus-, insect cell-, bacteria-, or plant-derived systems (Low et al, 2014 ; Pillet et al, 2016 ; Valero-Pacheco et al, 2016 ; Li et al, 2017 ). In a double-blind, randomized phase I clinical trial, Low and colleagues showed that a non-adjuvanted H1NIpdm09 VLP vaccine was safe and resulted in seroconversion in more than 50% of the subjects with just one dose, and this percentage increased after boost (Low et al, 2014 ).…”
Section: Efforts To Avert the Setbacks In Vaccine Usementioning
confidence: 99%
See 1 more Smart Citation
“…Although these are non-replicating particles, they retain the morphology of the virus and, therefore, the antigenicity and can activate innate immunity. VLPs can be produced in several expression systems, including baculovirus-, insect cell-, bacteria-, or plant-derived systems (Low et al, 2014 ; Pillet et al, 2016 ; Valero-Pacheco et al, 2016 ; Li et al, 2017 ). In a double-blind, randomized phase I clinical trial, Low and colleagues showed that a non-adjuvanted H1NIpdm09 VLP vaccine was safe and resulted in seroconversion in more than 50% of the subjects with just one dose, and this percentage increased after boost (Low et al, 2014 ).…”
Section: Efforts To Avert the Setbacks In Vaccine Usementioning
confidence: 99%
“…This cross-reactive response was also observed in chickens vaccinated with triple-subtype (H5, H7, and H9) VLPs that were protected against challenge with heterologous HPAI H5N2 and H7N3 and LPAI H9N2 (Pushko et al, 2017 ). Vaccination of chickens with adjuvanted VLPs expressing H9N2 HA and NA also induced robust HI antibodies and reduced viral shedding after homologous challenge (Li et al, 2017 ). In pigs, VLP antigens consisting of H1N1pdm09 HA, NA, and M1 proteins elicited robust levels of humoral and mucosal immune responses and protected pigs against homologous infection (Pyo et al, 2012 ).…”
Section: Efforts To Avert the Setbacks In Vaccine Usementioning
confidence: 99%
“…Since influenza virus is a huge threat to public health, flu VLP development has been a hot research topic in recent years. Influenza VLPs have been generated by co-expressing its structural proteins: matrix 1 (M1) + hemagglutinin (HA) [88] , [89] , HA + neuraminidase (NA) [90] , HA + NA + M1 [91] , [92] , [93] , or HA + NA + M1 + matrix 2 (M2) [94] . Influenza VLPs have been shown to induce protective immune responses and can serve as a platform for the expression of foreign proteins.…”
Section: Chimeric Cov-related Vlps and Their Prospects For Vaccinesmentioning
confidence: 99%
“…Intramuscular immunization with M8-VLP induced long-lasting protective antibody responses against influenza virus in mice. Intramuscular immunization with Freund's adjuvanted H9N2 influenza VLP containing HA and NA induced high levels of HAI titers with significant reduction in virus shedding and substantial homologous protection in chickens [88]. Adjuvants Alum, CpG DNA, monophosphoryl lipid A (MPL), poly IC, gardiquimod, and cholera toxin (CT) have been used to assess immunity in combination with influenza VLPs in mice [89].…”
Section: Chimeric Influenza or Adjuvanted Vlps Vaccinesmentioning
confidence: 99%